«Have fear of God! I am suffering»: mentally ill everyday life of the era of A.F. Kerensky. Anthropology of emotions - Z. M. Kobozeva; P. S. Kabytov (Вестник Самарского университета: История, педагогика, филология)
The article analyzes the emotional community of the Russian public, agitated by the pre-revolutionary sentiments, whose reaction was expressed in letters from citizens to A.F. Kerensky in 1917. The letters do not carry political ideas. They are all focused on the immediate emotions of the senders. During the formation of the file preserved in the GARF funds, all letters from citizens were divided into 2 groups. Letters from crazy people and letters from ordinary citizens. It is difficult to understand how and by whom this watershed was drawn between the mental norm and deviation from the norm. Therefore, this incident draws us not only to the problem of the «history of emotions», but also to the issue actualized in the works of M. Foucault: society and madness. Which was perceived as madness in one era or another. How clearly was insanity diagnosed in Russian society in 1917, as a disease, if any radical socio–political change forces people to live in a situation of a kind of insanity, when the norms of the old collapse and completely new texts of behavior and circumstances of life are created. How can a layman not go crazy? Or the letters to A.F. Kerensky are just a manifestation of the so-called «culture of the political», by which the «new social history» understands the daily political activity of the masses. This article actualizes the approach coming from the «history of emotions» to the analysis of the incident – letters of citizens to A.F. Kerensky.